2018
DOI: 10.1016/s2095-3119(18)62039-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of rhizobacteria in rice plants: Growth and mitigation of toxicity

Abstract: Allelopathic compounds reduce the growth and productivity of upland rice plants, especially in consecutive plantations. The rhizobacteria Pseudomonas fluorescens BRM-32111 and Burkholderia pyrrocinia BRM-32113 have been recorded as growth promoters in rice. This study was developed to understand the effect of the application of rhizobacteria on upland rice plants in consecutive plantations. Experiments were conducted in a completely randomized design with four replications of four treatments: rice seed inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Several authors have isolated different strains of Pseudomonas sp. from the rice rhizosphere and have reported significant increase in plant height, shoot and root dry weights, chlorophyll content and stress tolerance in Pseudomonas inoculated rice plants under traditional cultivation system compared to the uninoculated rice plants as a result of production of adequate amounts of phytohormones and considerable nitrogen fixation activity [16,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have isolated different strains of Pseudomonas sp. from the rice rhizosphere and have reported significant increase in plant height, shoot and root dry weights, chlorophyll content and stress tolerance in Pseudomonas inoculated rice plants under traditional cultivation system compared to the uninoculated rice plants as a result of production of adequate amounts of phytohormones and considerable nitrogen fixation activity [16,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…[15], Burkholderia sp. [16], Lysinibacillus sp. [17] have been isolated from the rhizosphere of upland rice varieties and have shown to be highly effective in growth promotion under greenhouse and field conditions.…”
mentioning
confidence: 99%
“…Soil bacterial community plays a key role in regulating soil processes and its composition determines agricultural soil sustainability (Rêgo et al, 2018). The straw return provides energy and nutrients for soil bacterial growth (Chen et al, 2017) and many studies have shown that straw return redistributes the soil bacterial community composition (Lu et al, 2015;Zhao et al, 2017;Su et al, 2020).…”
Section: The Effect Of Straw Return On Soil Microbial Community Compositionmentioning
confidence: 99%
“…Shahid and Khan found that due to inoculating chickpea with Burkholderia cepacia, a phosphate solubilizing and glyphosate-resistant bacterium, the concentrations of chlorophyll b, a, and carotenoid pigments were increased, as well as the negative effects of glyphosate on chickpea were decreased (Shahid and Khan 2018). In Rego and colleagues study, two rhizobacteria, including Pseudomonas fluorescens BRM-32111 and Burkholderia pyrrocinia BRM-32113, were isolated from rice rhizosphere, and their role on mitigation of toxic allelochemicals and crop yield were assessed in field experiment in the presence of allelopathic rice residues (Rêgo et al 2018). They found that rice inoculation ; cadmium, lead and arsenic resistant species, respectively, while applied on rice.…”
Section: Discussionmentioning
confidence: 99%